Psicologia e formação do pedagogo: análise da disciplina psicologia da educação na UFG/RC (1988/2014) - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Taking for granted that the Educational Psychology is a discipline with fundamental contribution to the training of teachers, especially the teachers – responsible for the initiation school in Early Childhood Education and Early Years of elementary school, and therefore appropriate to understand their role and place in teacher education, this study was proposed to analyze the contents and menus of Educational Psychology in the School of Education, with the cut out the provisions of the Project Curriculum Course offered in Universidade Federal de Goiás/ Regional Catalão, from 1988 to 2014. In terms of methodology the documentary and bibliographical research, priority documents as – menus and teaching plans as well as PPCs who instructed the format of the training of teachers in the investigated period. The literature review included authors like Demerval Saviani, Lourenço Filho, Iria Brzeniski, Bernadette Gatti, Priscila Larocca, Carmen Silva focusing on teacher training, with emphasis on different variables of the formation of the educator and the Pedagogy Course in Brazil in different spaces and times, providing an approach and dialogue with the theoretical production of the field. In this study it was found that over 25 years of Pedagogy course of the operation, the reference used in Educational Psychology had few modifications - even with transition periods - which suggests and indicates the need to review the purpose of this discipline. In the results, we noted numerous problems for the effective and contributory construction of discipline, among which stands out the relationship between theory and practice; the need for a better definition of the content and thematic units; overcoming the proposal for a psychology considered as a practice ground, disjointed contexts; the application of psychological theories and principles, though to signal the object of psychology science, need to talk and instruct targeted themes for teacher training, considering the nuances of the contexts, the historical and social circumstances. Above all, one sees that the Educational Psychology, as the foundation of teacher education, to broaden the debate and application of its principles around issues that mobilize the reality and the professional field of educator, permeated by difficulties and conflicts, with distinct problems in nature and complexity.
Psychology and the educator training: discipline analysis of educational psychology at UFG / RC (1988-2014)
Keywords: Formação de professores; Psicologia da educação; Pedagogia; Teacher training; Educational psychology; Pedagogy; EDUCACAO::ENSINO-APRENDIZAGEM